3M LiFSIPI3 composite in-situ polymer electrolyte and its preparation method
Patent Information
- Application Number
- CN202611099006.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-09
AI Technical Summary
但现有原位聚合物电解质普遍存在锂盐解离不充分、DOL单体聚合转化率低、电解质力学强度不足等问题,易诱发金属锂负极锂枝晶生成、电解质与电极界面阻抗偏大,导致电池循环稳定性差、安全风险高,难以满足实用化要求
[0013]基于以上方面,通过3MLiFSI与PI3协同调控,实现DOL快速高效开环聚合,聚合周期缩短至24h以内,所制电解质呈均匀无定形交联结构,PI3显著提升DOL聚合转化率与电解质致密度,同步强化离子传导与力学性能,有效降低电解质与金属锂的界面阻抗,从根源抑制锂枝晶生长,大幅提升界面稳定性与电池安全性能。该复合原位聚合物电解质兼具宽电化学窗口与优异循环、倍率性能,电化学稳定窗口达5.15V(vs.Li/Li+),可匹配高电压正极材料;Li对称电池在2.0mA・cm-2下稳定循环600h,LFP全电池1C倍率循环500周容量保持率94.2%、平均库伦效率99.8%,且电解质膜可拉伸至原尺寸4倍并具备弹性恢复能力,能适配锂负极充放电体积变化,全面提升锂金属电池的使用寿命与实用化潜力。
Smart Images

Figure CN122889832A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite in-situ polymer electrolyte technology, and particularly relates to 3MLiFSIPI3 composite in-situ polymer electrolyte and its preparation method. Background Technology
[0002] Solid-state lithium batteries, with their high energy density and high safety characteristics, have become a core research and development direction in the fields of power batteries and energy storage. In-situ polymer electrolytes are considered a key technology route for solid-state electrolytes due to their simple preparation process and excellent electrode interface compatibility. However, existing in-situ polymer electrolytes generally suffer from problems such as insufficient lithium salt dissociation, low DOL monomer polymerization conversion rate, and insufficient electrolyte mechanical strength. They are prone to inducing lithium dendrite formation in the lithium metal anode and have high impedance at the electrolyte-electrode interface, resulting in poor battery cycle stability and high safety risks, making it difficult to meet practical application requirements. Current in-situ polymer electrolyte systems mostly use a single lithium salt to initiate polymerization, lacking efficient modifiers to synergistically regulate reaction kinetics and microstructure, and cannot simultaneously achieve high ionic conductivity, a wide electrochemical stability window, and good mechanical toughness. At the same time, they have defects such as long polymerization cycles, poor film uniformity, and weak resistance to high-voltage oxidation, making it difficult to match with high-voltage cathode materials and limiting their large-scale application in high-energy-density lithium metal batteries. Summary of the Invention
[0003] In view of the aforementioned problems, and in conjunction with the first aspect of the present invention, embodiments of the present invention provide a 3M LiFSIPI3 composite in-situ polymer electrolyte, the method comprising: It is prepared by in-situ polymerization of the following components: The polymer matrix is a mixture of thermoplastic polyurethane and 1,3-dioxolane / ethylene glycol dimethyl ether solvent, wherein the volume ratio of DOL to DME is 1:1, and the TPU mass percentage is 15%. The lithium salt is lithium bis(fluorosulfonyl)imide at a concentration of 3M; The modifier is phosphorus triiodide at a mass ratio of 0.01%.
[0004] The preparation method of 3MLiFSIPI3 composite in-situ polymer electrolyte includes the following steps: Add 15% by weight of TPU to a mixed solvent of DOL / DME in a volume ratio of 1:1, stir at a constant temperature until completely dissolved, and then cool to room temperature; Add 0.01% PI3 by mass to the above solution and stir at room temperature until a homogeneous solution is formed; Add 3M LiFSI and carry out in-situ polymerization at room temperature; An electrolyte membrane was prepared by coating and then vacuum dried to obtain a 3M LiFSIPI3 composite in-situ polymer electrolyte.
[0005] Preferably, the constant temperature in step one is 50°C and the stirring time is 4 hours.
[0006] Preferably, the stirring time at room temperature in step two is 30 minutes, and the resulting solution is a light green transparent solution.
[0007] Preferably, in-situ polymerization in step three does not require an additional catalyst, and the polymerization cycle is ≤24h.
[0008] Preferably, the thickness of the electrolyte membrane in step four is controlled at 20–50 μm.
[0009] Preferably, the electrochemical stability window of the electrolyte is approximately 5.15V.
[0010] Preferably, the electrolyte assembly forms a Li / electrolyte / Li symmetric battery at 25°C and 2.0 mA·cm⁻¹. -2 Under certain conditions, it can be stably cycled for 600 hours.
[0011] Preferably, the electrolyte assembly of the LiFePO4 / electrolyte / Li full cell can be stably cycled for 500 cycles at 1C rate at room temperature, with a capacity retention of 94.2% and an average coulombic efficiency of 99.8%.
[0012] Preferably, the electrolyte membrane can elongate to four times its original size upon breakage, exhibiting elastic recovery properties.
[0013] Based on the above, rapid and efficient ring-opening polymerization of DOL was achieved through the synergistic regulation of 3MLiFSI and PI3, shortening the polymerization cycle to less than 24 hours. The resulting electrolyte exhibits a uniform amorphous cross-linked structure. PI3 significantly improves the polymerization conversion rate and electrolyte density of DOL, simultaneously enhancing ion conduction and mechanical properties, effectively reducing the interfacial impedance between the electrolyte and lithium metal, suppressing lithium dendrite growth at its source, and greatly improving interfacial stability and battery safety. This composite in-situ polymer electrolyte combines a wide electrochemical window with excellent cycle and rate performance, achieving an electrochemical stability window of 5.15V (vs. Li / Li). + It can be matched with high-voltage cathode materials; Li symmetric cells at 2.0 mA·cm -2 After 600 hours of stable cycling, the LFP full cell maintains a capacity retention of 94.2% and an average coulombic efficiency of 99.8% after 500 cycles at 1C rate. Furthermore, the electrolyte membrane can be stretched to 4 times its original size and has elastic recovery capability, which can adapt to the volume changes of lithium anode during charging and discharging, thus comprehensively improving the service life and practical application potential of lithium metal batteries. Attached Figure Description
[0014] Figure 1 This is a flowchart of the preparation process of 3MLiFSI-PI3 composite in-situ polymer electrolyte provided in the embodiments of the present invention; Figure 2This is a polymerization time diagram of 3MLiFSI and 3MLiFSI-PI3 provided in the embodiments of the present invention; Figure 3 This is a SEM image of the 3M LiFSI-PI3 composite in-situ polymer electrolyte provided in an embodiment of the present invention; Figure 4 The FTIR of 3M LiFSI and 3M LiFSI-PI3 provided in the embodiments of the present invention; Figure 5 This is a cycle performance diagram of a Li / 3MLiFSI-PI3 / Li symmetric battery provided in an embodiment of the present invention; Figure 6 This is a cycle performance diagram of the LFP / 3MLiFSI-PI3 / Li full cell provided in an embodiment of the present invention; Figure 7 The mechanical properties of the 3M LiFSI-PI3 composite in-situ polymer electrolyte provided in this embodiment of the invention are shown in the diagram. Figure 8 This is an electrochemical stability window diagram of the 3MLiFSI composite in-situ polymer electrolyte and the 3MLiFSI-PI3 composite in-situ polymer electrolyte provided in the embodiments of the present invention; Figure 9 The battery rate performance diagrams of the 3MLiFSI composite in-situ polymer electrolyte and the 3MLiFSI-PI3 composite in-situ polymer electrolyte provided in the embodiments of the present invention are shown. Detailed Implementation
[0015] The present invention will now be described in detail with reference to the accompanying drawings.
[0016] This invention addresses the performance defects of existing in-situ polymer electrolytes through a composite technology solution of LiFSI concentration optimization and PI3 doping modification. Specific technical features are as follows: 1. Composition of the electrolyte system: Polymer matrix: thermoplastic polyurethane (TPU) + DOL / ethylene glycol dimethyl ether (DME) mixed solvent (volume ratio 1:1), with TPU accounting for 15% by mass, providing mechanical support and a flexible skeleton; Lithium salt system: 3M concentration LiFSI is used, which combines the functions of lithium source and DOL ring-opening polymerization catalyst to achieve high dissociation efficiency; Modifier: Add 0.01% by mass of PI3 as a polymerization accelerator and mechanical enhancer to regulate the polymerization reaction rate and electrolyte microstructure.
[0017] Preparation process: (1) Dissolution: Add 15% by mass of TPU to the DOL / DME mixed solvent, stir at 50°C for 4 hours until completely dissolved, and cool to room temperature; (2) Doping: Add 0.01% by mass of PI3 and stir at room temperature for 30 min until a uniform light green solution is formed; (3) Polymerization: Add 3M LiFSI and polymerize in situ at room temperature without the need for additional catalysts, shortening the polymerization cycle to less than 24 hours; (4) Film formation: Electrolyte membranes were prepared by coating method, with the thickness controlled at 2050 μm, and then dried under vacuum for later use.
[0018] 3. Performance regulation principle: LiFSI concentration optimization: 3M LiFSI can maximize lithium salt dissociation efficiency, form a stable ion conduction network, and broaden the electrochemical stability window; PI3 doping functions as a Lewis acid to promote the ring-opening polymerization of DOL, improve the conversion rate of chain DOL, and enhance the compactness of the electrolyte structure; at the same time, it improves mechanical properties and inhibits lithium dendrite growth through inorganic-organic composite effects. Interface optimization: The in-situ polymerization process forms a cross-linked network structure, which reduces the interfacial impedance between the electrolyte and lithium metal and improves interfacial compatibility. Detailed Implementation
[0019] (1) Reagents and instruments: Reagents: LiFSI (battery grade, Shenzhen Xinzhoubang), TPU (Dongguan Zhongyuan Plastics), DOL (99.8%, Beijing Innoka), DME (99.5%, Beijing Innoka), PI3 (99%, Aldrich), lithium metal sheet (battery grade, Tianjin Zhongneng Lithium Industry). Instruments: Thermostatic magnetic stirrer (SN-MS-1, Shanghai Shangshan), vacuum glove box (Lab2000, Etelux), electrochemical workstation (Chenhua CHI760E), scanning electron microscope (Hitachi S-3400N), X-ray diffractometer (Rigaku ULTIMAIV).
[0020] (2) Preparation steps: 1. Accurately weigh 0.2998g TPU, add 1.999g DOL / DME mixed solvent (volume ratio 1:1), place in a 50℃ constant temperature magnetic stirrer and stir for 4h until the TPU is completely dissolved, then cool to room temperature; 2. Add 0.0003 g PI3 to the above solution and stir at room temperature for 30 min to form a uniform light green transparent solution; 3. Slowly add 3M LiFSI solution and stir continuously for 10 minutes. Pour the mixture into a polytetrafluoroethylene mold and let it stand at room temperature in a vacuum glove box for 24 hours to complete in-situ polymerization and form a solid electrolyte membrane. 4. Use a button cell punching machine (MRX-CP60) to punch the electrolyte membrane into round pieces with a diameter of 32mm, and set them aside.
[0021] (3) Performance testing: Lithium stability test: Assemble a Li / electrolyte / Li symmetric battery and perform constant current charge-discharge cycles at 25℃ and 2.0mA·cm⁻², and record the changes in polarization potential; Mechanical property testing: The elongation at break and elastic recovery of the electrolyte membrane were tested using a tensile testing machine; Electrochemical performance testing: Assemble a LiFePO4 (LFP) / electrolyte / Li full cell and test its cycle performance, rate performance and electrochemical stability window.
[0022] like Figure 1 As shown, 15% TPU by mass was dissolved in a 1:1 volume ratio of DOL and DME, and stirred at 50°C for 4 hours to ensure complete dissolution of the TPU. After cooling to room temperature, 0.01% PI3 by mass was added, and the mixture was stirred at room temperature for 30 minutes to ensure complete dissolution of the PI3, resulting in a light green solution. Subsequently, 3M LiFSI was added.
[0023] like Figure 2 As shown, LiFSI acts as an initiator to induce the ring-opening polymerization of DOL and also provides lithium ions to the electrolyte as a lithium source. PI3, as an inorganic particle, not only improves the mechanical properties of the electrolyte but also enables DOL to undergo ring-opening polymerization more quickly, shortening the curing time.
[0024] like Figure 3 As shown, the absence of particulate matter on the electrolyte membrane surface indicates that PI3 is completely dissolved and uniformly dispersed, suggesting that the 3MLiFSI-PI3 composite in-situ polymer electrolyte is amorphous. Compared to the 3MLiFSI composite in-situ polymer electrolyte, the 3MLiFSI-PI3 composite in-situ polymer electrolyte exhibits more pronounced and uniform wrinkles. The reasons are as follows: Firstly, the addition of PI3 accelerates the polymerization rate of DOL, preventing the 3MLiFSI-PI3 composite in-situ polymer electrolyte surface from spreading evenly and smoothly; secondly, PI3 increases the conversion rate of DOL ring-opening polymerization, intensifying the cross-linking overlap between polymer segments, resulting in more wrinkles on the surface of the 3MLiFSI-PI3 composite in-situ polymer electrolyte.
[0025] like Figure 4 As shown, by comparing the infrared spectra of 3MLiFSI-PI3 with those of 3MLiFSI-PI3, it can be seen that the spectrum of 3MLiFSI is basically the same as that of 3MLiFSI-PI3, with no disappearance or appearance of characteristic absorption peaks, indicating that the addition of a small amount of PI3 has no effect on the structure of the electrolyte. The structure of 3MLiFSI is the same as that of 3MLiFSI-PI3, which is a cross-linked structure.
[0026] like Figure 5 As shown, the Li / 3MLiFSI / Li battery can only cycle for 170 hours, while the Li / 3MLiFSI-PI3 / Li battery can cycle stably for 600 hours. This is due to two reasons: First, the addition of PI3 increases the ionic conductivity of the electrolyte, reduces the Li+ concentration gradient at the interface, promotes uniform and stable Li+ deposition on the lithium surface, and reduces lithium dendrite formation. Second, inorganic PI3 particles have higher mechanical strength than organic materials, and PI3 improves the conversion rate of chain-like DOLs, making the 3MLiFSI-PI3 composite in-situ polymer electrolyte structure more stable and dense, with higher mechanical strength. Therefore, the 3MLiFSI-PI3 composite in-situ polymer electrolyte, with its high ionic conductivity and mechanical strength, is more stable with metallic lithium and has a longer cycle life.
[0027] like Figure 6 The figure shows the cycling performance of LFP / 3MLiFSI-PI3 / Li at room temperature and 1C. The figure shows that the battery can stably cycle for 500 cycles. The battery capacity gradually increases in the first few weeks, which is the electrode activation process. After stabilization, the reversible discharge specific capacity of LFP / 3MLiFSI-PI3 / Li is 137.1 mAh g⁻¹, and it still retains 94.2% of its capacity after 500 cycles, with an average coulombic efficiency of 99.8%.
[0028] like Figure 7 As shown in the figure, the electrolyte membrane can be stretched to four times its original size. When the tension is removed, the electrolyte membrane returns to its original shape, indicating that the 3MLiFSI-PI3 composite in-situ polymer electrolyte has good elasticity, which can effectively suppress the volume expansion of lithium metal during charging and discharging, reduce dendrite growth, and improve battery life.
[0029] like Figure 8 As shown in the figure, the 3M LiFSI-PI3 composite in-situ polymer electrolyte exhibits higher stability than the 3M LiFSI composite in-situ polymer electrolyte, with a decomposition voltage of approximately 5.15V (vs. Li / Li+). This is due to two main reasons: first, the addition of PI3, as inorganic compounds have a higher decomposition voltage than organic compounds; and second, PI3 improves the ring-opening conversion rate of DOL. DOL itself has an unstable cyclic structure and poor resistance to high-pressure oxidation. After ring-opening polymerization, the structural stability of DOL is greatly improved, significantly enhancing its resistance to high-pressure oxidation. Therefore, the 3M LiFSI-PI3 composite in-situ polymer electrolyte has a wider electrochemical stability window.
[0030] like Figure 9As shown in the figure, at 0.1C, the specific capacities of the two batteries are not significantly different. This is because the electric field strength is low at low current densities, and the migration rates of Li+ are similar, resulting in similar discharge specific capacities at low currents. However, as the current density increases, the 3MLiFSI-PI3 composite in-situ polymer electrolyte, with its higher ionic conductivity, exhibits better rate performance. At a high current of 1C, the 3MLiFSI composite in-situ polymer electrolyte lacks sufficient mechanical strength to suppress lithium dendrite growth, thus failing to achieve stable cycling. Therefore, the LFP / 3MLiFSI-PI3 / Li battery, with its superior mechanical properties and conductivity, can cycle stably at 1C. When the current returns to 0.1C, the specific capacity of the LFP / 3MLiFSI-PI3 / Li battery recovers, indicating good reversibility.
[0031] It should be noted that, in order to simplify the description of the present invention and thus help to understand one or more embodiments of the invention, multiple features may sometimes be grouped into one embodiment, drawing or description thereof in the foregoing description of the embodiments of the present invention.
[0032] The embodiments of this application have been described above with reference to the accompanying drawings. Unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other. This application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of this application.
Claims
1. 3M LiFSIPI3 composite in-situ polymer electrolyte, characterized in that: It is prepared by in-situ polymerization of the following components: The polymer matrix is a mixture of thermoplastic polyurethane and 1,3-dioxolane / ethylene glycol dimethyl ether solvent, wherein the volume ratio of DOL to DME is 1:1, and the TPU mass percentage is 15%. The lithium salt is lithium bis(fluorosulfonyl)imide at a concentration of 3M; The modifier is phosphorus triiodide at a mass ratio of 0.01%. A method for preparing a 2.3M LiFSIPI3 composite in-situ polymer electrolyte, characterized by comprising the following steps: Add 15% by weight of TPU to a mixed solvent of DOL / DME in a volume ratio of 1:1, stir at a constant temperature until completely dissolved, and then cool to room temperature; Add 0.01% PI3 by mass to the above solution and stir at room temperature until a homogeneous solution is formed; Add 3M LiFSI and carry out in-situ polymerization at room temperature; An electrolyte membrane was prepared by coating and then vacuum dried to obtain a 3M LiFSIPI3 composite in-situ polymer electrolyte.
3. The method for preparing 3M LiFSIPI3 composite in-situ polymer electrolyte according to claim 2, characterized in that: In step one, the constant temperature is 50℃ and the stirring time is 4 hours.
4. The method for preparing 3M LiFSIPI3 composite in-situ polymer electrolyte according to claim 2, characterized in that: In step two, the stirring time at room temperature is 30 minutes, and the resulting solution is a light green transparent solution.
5. The method for preparing 3M LiFSIPI3 composite in-situ polymer electrolyte according to claim 2, characterized in that: In step three, in-situ polymerization requires no additional catalyst, and the polymerization cycle is ≤24h.
6. The method for preparing 3M LiFSIPI3 composite in-situ polymer electrolyte according to claim 2, characterized in that: In step four, the thickness of the electrolyte membrane is controlled at 20–50 μm.
7. The 3M LiFSIPI3 composite in-situ polymer electrolyte and its preparation method according to claim 1, characterized in that: The electrolyte has an electrochemical stability window of approximately 5.15 V.
8. The method for preparing 3M LiFSIPI3 composite in-situ polymer electrolyte according to claim 1, characterized in that: The electrolyte assembly forms a Li / electrolyte / Li symmetric battery, operating at 25°C and 2.0 mA·cm⁻¹. -2 Under certain conditions, it can be stably cycled for 600 hours.
9. The method for preparing 3M LiFSIPI3 composite in-situ polymer electrolyte according to claim 1, characterized in that: The electrolyte assembly of the LiFePO4 / electrolyte / Li full cell can be stably cycled for 500 cycles at 1C rate at room temperature with a capacity retention of 94.2% and an average coulombic efficiency of 99.8%.
10. The method for preparing 3M LiFSIPI3 composite in-situ polymer electrolyte according to claim 1, characterized in that: The electrolyte membrane can elongate up to four times its original size upon breakage and has elastic recovery properties.